Perspectives on ethical hacking and penetration testing - Kaushik, Keshav; Bhardwaj, Akashdeep 1971- (IGI Global, 2023)
Cybersecurity has emerged to address the need for connectivity and seamless integration with other devices and vulnerability assessment to find loopholes. However, there are potential challenges ahead in meeting the growing need for cybersecurity. This includes design and implementation challenges, application connectivity, data gathering, cyber-attacks, and cyberspace analysis. Perspectives on Ethical Hacking and Penetration Testing familiarizes readers with in-depth and professional hacking and vulnerability scanning subjects. The book discusses each of the processes and tools systematically and logically so that the reader can see how the data from each tool may be fully exploited in the penetration test's succeeding stages. This procedure enables readers to observe how the research instruments and phases interact. This book provides a high level of understanding of the emerging technologies in penetration testing, cyber-attacks, and ethical hacking and offers the potential of acquiring and processing a tremendous amount of data from the physical world. Covering topics such as cybercrimes, digital forensics, and wireless hacking, this premier reference source is an excellent resource for cybersecurity professionals, IT managers, students and educators of higher education, librarians, researchers, and academicians.
Includes bibliographical references and index
Keywords: Penetration testing (Computer security); Computer crimes -- Prevention; Computersicherheit; Social Engineering -- Sicherheit; Computerkriminalität & Hacking; Bioethik, Tierethik